2018
DOI: 10.3389/fmicb.2018.02961
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of the 5-Amino-1-(Carbamoylmethyl)-1H-1,2,3-Triazole-4-Carboxamide Scaffold to Disarm the Bacterial SOS Response

Abstract: Many antibiotics, either directly or indirectly, cause DNA damage thereby activating the bacterial DNA damage (SOS) response. SOS activation results in expression of genes involved in DNA repair and mutagenesis, and the regulation of the SOS response relies on two key proteins, LexA and RecA. Genetic studies have indicated that inactivating the regulatory proteins of this response sensitizes bacteria to antibiotics and slows the appearance of resistance. However, advancement of small molecule inhibitors of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Recently, it has been demonstrated that some drugs used for cancer therapy can also enhance the emergence of resistant strains, through the induction of the SOS pathway [25]. This panorama suggests that SOS-related proteins are interesting targets for the development of drug helpers, and it has encouraged the search of compounds able to inhibit this pathway [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that some drugs used for cancer therapy can also enhance the emergence of resistant strains, through the induction of the SOS pathway [25]. This panorama suggests that SOS-related proteins are interesting targets for the development of drug helpers, and it has encouraged the search of compounds able to inhibit this pathway [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“… Protein Inhibitor Proposed mechanism of action Ref. SSB Small molecules Disrupt SSB protein interfaces [27] RecBCD sulfanyltriazolobenzimidazole NSAC1003 Acts on RecB ATP-binding site [29] PolV RecAD112R/N113R Acts on UmuD ATP-binding site [16] LexA 5-amino-1-(carbamoylmethyl)-1H-1,2,3-triazole-4-carboxamide This effect appears specific for the self-cleavage activity of LexA [33] , [34] Boron-containing compounds interact with the catalytic Ser-119 (act as inhibitors of LexA self-cleavage) [31] RecA peptide (N-terminal helix) N-terminal helix disrupt protein interfaces [77] compounds, suramin-like agents ATPase inhibitors [70] 2-amino-4,6-diarylpyridine ATPase inhibitors [72] compounds, 33 unique scaffold groups inhibitors with varied specificity for RecA conformation [63] suramin disassemble RecA-single-stranded DNA filaments [61] Zinc acetate inhibitor of LexA cleavage [69] Compounds (A03, A10) disrupt ssDNA binding [76] epiphorellic acid/divaricatic, perlatolic, alpha-collatolic, lobaric, lichesterinic, protolichesterinic binds the ssDNA binding site inhibitors for ATP binding site [62] peptide 4E1 (RecX) RecX-like disassemble RecA-single-stranded DNA filaments [85]
Fig. 1 Surface view of two turns of RecA filaments built on a single-strand DNA...
…”
Section: Targetsmentioning
confidence: 99%
“…In another approach screening compounds for LexA self-cleavage blocking revealed an active substance 5-amino-1-(carbamoylmethyl)-1H-1,2,3-triazole-4-carboxamide [33] . This work led to the identification of an analogue with improved activity and an expanded spectrum of applications [34] .…”
Section: Targetsmentioning
confidence: 99%
“…While the molecular interface of RecA* with LexA that governs SOS activation remains poorly understood, both have been successfully targeted with small molecules. DISARMERs, 'drugs that inhibit SOS activation to repress mechanisms enabling resistance', have been uncovered through various screening approaches [52][53][54]. Although RecA is likely a less ideal target than LexA (below), small molecules that inhibit RecA polymerization have been identified, with some classes appearing to slow fluoroquinolone-associated mutagenesis [54].…”
Section: Sos Regulators: Reca and Lexamentioning
confidence: 99%
“…Although RecA is likely a less ideal target than LexA (below), small molecules that inhibit RecA polymerization have been identified, with some classes appearing to slow fluoroquinolone-associated mutagenesis [54]. High-throughput screening for inhibitors of LexA cleavage has also revealed several classes of leads that can target the RecA*/LexA axis in vitro and prevent SOS activation in cells, including optimized leads that reduce mutagenesis and acquired resistance associated with antibiotic exposure [52,53].…”
Section: Sos Regulators: Reca and Lexamentioning
confidence: 99%